Migration of Employees from Ukraine – Cultural Proximity and Human Resources Management Practices as a Chance to Keep them in Poland - Gadomska-Lila, Katarzyna; Moskalenko, Viktoriia (Facets of Managing in Cross-Cultural Diversity, 2021)
The purpose of this chapter is to identify the reasons for the emigration of Ukrainian employees and to explain the importance of cultural proximity and human resources practices whose aim is to keep them in Polish organisations. The considerations are based on a desk research analysis of migrations of Ukrainians, and on the results of quantitative empirical research conducted by the Authors regarding national cultures, values related to work and managing human resources. The research results allowed to determine problems faced by Ukrainian workers employed in Poland, as well as human resource management practices to help overcome them. The study shows that cultural proximity, linguistic similarity or common history favour the choice of Poland as the direction of migration for Ukrainians, and human resources management practices of Polish employers favour quick implementation to work in Poland.